Modulation of p38 MAP kinase activity in regulatory T cells after tolerance with anti-DNA Ig peptide in (NZB × NZW)F(1) lupus mice - Lourenço, Elaine V. (2009)
Treatment of (NZB × NZW)F(1) (NZB/W) lupus-prone mice with the anti-DNA Ig-based peptide pCons prolongs the survival of treated animals and effectively delays the appearance of autoantibodies and glomerulonephritis. We have previously shown that part of these protective effects associated with the induction of CD4(+)CD25(+)Foxp3(+) regulatory T cells (Tregs) that suppressed autoantibody responses. Since the effects of pCons appeared secondary to qualitative rather than quantitative changes in Tregs, we investigated the molecular events induced by tolerance in Tregs and found that signaling pathways including ZAP70, p27, STAT1, STAT3, STAT6, SAPK, ERK and JNK were not significantly affected. However, peptide tolerization affected in Tregs the activity of the mitogen-activated protein kinase p38, whose phosphorylation was reduced by tolerance. The pharmacologic inhibition of p38 with the pyridinyl imidazole inhibitor SB203580 in naïve NZB/W mice reproduced in vivo the effects of peptide-induced tolerance and protected mice from lupus-like disease. Transfer experiments confirmed the role of p38 in Tregs on disease activity in the NZB/W mice. These data indicate that the modulation of p38 activity in lupus Tregs can significantly influence the disease activity.